2021
DOI: 10.1177/2470547021996006
|View full text |Cite
|
Sign up to set email alerts
|

The Reward System and Post-Traumatic Stress Disorder: Does Trauma Affect the Way We Interact With Positive Stimuli?

Abstract: Post-traumatic stress disorder (PTSD) is a highly prevalent disorder and a highly debilitating condition. Although anhedonia is an important construct of the disorder, the relationship between PTSD and reward functioning is still under-researched. To date, the majority of research on PTSD has focused on fear: fear learning, maintenance, and extinction. Here we review the relevant literature—including clinical observations, self-report data, neuroimaging research, and animal studies—in order to examine the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 123 publications
0
21
0
Order By: Relevance
“…While the role of the Negative Valence System in anxiety is robustly consolidated, most studies disregarded the involvement of the Positive Valence System in individuals with anxiety symptoms. At the same time, although some studies reported reduced processing of pleasant and rewarding stimuli in individuals with PTSD (e.g., Nawijn et al, 2015 ; Kalebasi et al, 2015 ; Seidemann et al, 2021 ), it is unclear whether this effect is produced by trauma exposure or, rather, represents a vulnerability factor. Of note, the present finding suggests that the interaction between blunted processing of pleasant images and anxiety symptoms may represent a preexisting risk factor for PTSS severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the role of the Negative Valence System in anxiety is robustly consolidated, most studies disregarded the involvement of the Positive Valence System in individuals with anxiety symptoms. At the same time, although some studies reported reduced processing of pleasant and rewarding stimuli in individuals with PTSD (e.g., Nawijn et al, 2015 ; Kalebasi et al, 2015 ; Seidemann et al, 2021 ), it is unclear whether this effect is produced by trauma exposure or, rather, represents a vulnerability factor. Of note, the present finding suggests that the interaction between blunted processing of pleasant images and anxiety symptoms may represent a preexisting risk factor for PTSS severity.…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with an alteration of the Negative Valence System domain of the Research Domain Criteria (RDoC), a clinical research model developed to better characterize the affective, cognitive, and physiological factors underlying psychopathology ( Insel, 2010 ; Kozak and Cuthbert, 2016 ). In addition, several studies suggest that PTSD might be characterized by an alteration of the Positive Valence System of the RDoC matrix, indicated by anhedonia, feelings of detachment from others, and a reduced reward-seeking behavior ( Elman et al, 2005 ; Nawijn et al, 2015 ; Kalebasi et al, 2015 ; Sailer et al, 2008 ; Seidemann et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study using the Reading the Mind in the Eyes Task (RMET), a theory of mind task, women with PTSD stemming from childhood trauma demonstrated slower RMET reaction times to both positive and negative emotionally valenced states (Nazarov et al., 2014). Most recently, a review of PTSD and reward functioning (Seidermann et al., 2021) highlighted how most research on PTSD has focused on fear, stressing the need for further study of the complex association between reward system functioning and trauma exposure.…”
Section: Ptsd and Happy Face Processingmentioning
confidence: 99%
“…More recent work suggests that PTSD might also involve abnormalities in the PVS, as indicated by deficient reward anticipation, decreased approach (reward-seeking) behavior, and diminished hedonic responses to rewarding outcomes 32,33 . Reward processing is known to involve the meso-corticolimbic pathway, represented by dopamine projections from the ventral tegmental area (VTA) to the ventral striatum (VS), including the nucleus accumbens (NAcc), and further to ventromedial/orbital frontal brain structures 34,35 .…”
Section: Introductionmentioning
confidence: 99%